1983
DOI: 10.1111/j.1540-6261.1983.tb03623.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fiscal and Monetary Linkage between Stock Returns and Inflation

Abstract: Contrary to economic theory and common sense, stock returns are negatively related to both expected and unexpected inflation. We argue that this puzzling empirical phenomenon does not indicate causality.Instead, stock returns are negatively related to contemporaneous changes in expected inflation because they signal a chain of events which results in a higher rate of monetary expansion. Exogenous shocks in real output, signalled by the stock market, induce changes in tax revenue, in the deficit, in Treasury bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
107
1
9

Year Published

1987
1987
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(128 citation statements)
references
References 23 publications
11
107
1
9
Order By: Relevance
“…Fischer and Merton (1984), using annual US data over the period , found that the stock market contributes substantially to the prediction of the growth rate of real GNP. Barro (1990) arrived at similar conclusions regarding US investment over several sample periods: 1891-1914, 1921-1940& 1948-1987. Geske and Roll (1983, along with Fama (1990) and Schwert (1990), also found strong relations between stock returns and real activity.…”
Section: Introductionmentioning
confidence: 52%
“…Fischer and Merton (1984), using annual US data over the period , found that the stock market contributes substantially to the prediction of the growth rate of real GNP. Barro (1990) arrived at similar conclusions regarding US investment over several sample periods: 1891-1914, 1921-1940& 1948-1987. Geske and Roll (1983, along with Fama (1990) and Schwert (1990), also found strong relations between stock returns and real activity.…”
Section: Introductionmentioning
confidence: 52%
“…Previous studies like Fama (1981), Geske& Roll (1983, and Chen, Roll, & Ross (1986), among others, have indicated a link between increased volatility in the stock market and movement of macroeconomic variables. Therefore, it is important to explore similar in Nepalese stock market.…”
Section: Introductionmentioning
confidence: 90%
“…This may reduce the tendency of investors to borrow and invest in stocks, and raises the cost of doing business and hence affects profit margin. On the contrary, lower interest rates resulting from expansionary monetary policy boosts stock market (Fama, 1981;Geske& Roll, 1983) and contrary to this Kuwarnu& Victor (2011), and Chia & Lim (2015) revealed the positive relation.…”
Section: Research Gapmentioning
confidence: 96%
“…Fama [15] found that the growth rate of industrial production has a strong contemporaneous link with stock returns. Geske and Roll [20], Fama [16] and Tainer [43] assumed a similar positive relationship taking into account the impact of industrial production on future cash flows. Chen et al [7] indicated that future growth in industrial production was a significant factor which affected stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%